Mathematics Interest and Reading Comprehension as Correlates of Elementary Students’ Mathematics Problem-Solving Skills - Nahdi, Dede Salim; Cahyaningsih, Ujiati; Jatisunda, Mohamad Gilar; Rasyid, Abdur (Papanda Publisher, 2024)
In the rapidly changing global landscape, adaptability to new challenges is essential. Mathematics, recognized as a key contributor to problem-solving skills, holds significant importance in navigating unfamiliar situations. This study delves into the correlation between mathematics interest, reading comprehension, and mathematical problem-solving abilities among elementary school students. Employers and academic institutions increasingly emphasize the application of mathematical knowledge in diverse scenarios, prompting educational reforms prioritizing problem-solving skills.The investigation involved 76 elementary students in Majalengka Regency, Indonesia, exploring mathematics interest, reading comprehension, and problem-solving skills using questionnaires and tests. Findings unveiled a noteworthy positive correlation between reading comprehension and mathematical problem-solving, surpassing the correlation with mathematics interest. Regression analysis reinforced this, highlighting the collective substantial impact of mathematics interest and reading comprehension on students' problem-solving proficiency.This study underscores the crucial role of reading comprehension in interpreting narrative-based mathematical problems. Understanding textual content significantly influences problem-solving strategies. Moreover, affective abilities, particularly mathematics interest, contribute significantly to problem-solving skills. A heightened interest in mathematics enhances motivation, encourages deeper conceptual learning, and fosters creativity in problem-solving.These results underscore the necessity of a holistic approach to mathematics education. Addressing not only cognitive aspects but also affective and reading proficiency facets can substantially enhance students' mathematical problem-solving abilities. Understanding the interrelationship among mathematics interest, reading comprehension, and affective abilities can pave the way for more effective teaching methodologies and improved academic outcomes in mathematics.